Blind stick with led and ultrasonic sensor technology - Jambari, Hanifah; Abdul Majid, Abdul Bariq Hamzi; Che Nan, Muhammad Syahmi (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The development of the Blind Stick with LED and Ultrasonic Sensor Technology is an innovative assistive device designed to enhance the mobility and safety of visually impaired individuals. By integrating ultrasonic sensors, this smart cane detects obstacles in the user’s path, providing real-time feedback through a combination of audible alerts and visual LED signals. The stick also features a lighting system that illuminates the user's environment, improving visibility in low-light conditions. This project explores the design, method, potential benefits, novelty, and commercial opportunities of the blind stick. The solution not only aims to improve the quality of life for visually impaired individuals but also offers a significant contribution to inclusive technology and social innovation.